3D-printed Mg-incorporated PCL-based scaffolds improves rotator cuff tendon-bone healing through regulating macrophage polarization - Wang, Tao; Yu, Ziqing; Lin, Shaozhang; Chen, Zhaohuan; Jin, Han; Liang, Lin; Zhang, Zhi-Yong (Frontiers in Bioengineering and Biotechnology, 2024)
Rotator cuff tear (RCT) is a frequent cause of shoulder pain and limited mobility. In recent years, tissue engineering of rotator cuff tendon-bone interfaces has emerged as a promising strategy to enhance tendon-bone healing. Poly(ε-caprolactone) (PCL), a synthetic polyester material, has been extensively used in orthopedic repair due to its slow degradation, good biocompatibility, and lack of biological toxicity. However, PCL alone does not provide sufficient compression resistance for use in RCT repair.Magnesium (Mg), as a fundamental component of bone, possesses natural antibacterial properties that promote bone differentiation, cell proliferation, and compressive resistance. Therefore, the objective of this project was to investigate whether the newly developed 3D-printed Mg-incorporated PCL-based scaffolds could enhance RCT-Repair augmentation. It was found that when incorporated with 10% Mg, PCL-based scaffolds exhibited the optimal bone repairing ability in vitro and in vivo. The in vitro experiments indicated that the successfully constructed 10Mg/PCL scaffolds enhance osteogenic activities and anti-inflammatory properties. Besides, the in vivo studies demonstrated that 10Mg/PCL scaffolds promoted tissue ingrowth and enhanced biocompatibility compared to the control PCL scaffolds. Furthermore, the 10Mg/PCL scaffolds enhanced the macrophages' ability to polarize towards the M2 subtype and inhibited inflammation signaling activation. This has the potential to improve the outcomes of RCT repair. These findings suggest that 3D-printed Mg-incorporated PCL-based scaffolds have the potential to improve rotator cuff healing by enhancing osteogenesis, reducing inflammation, and promoting macrophage polarization.